Nos(dos) meandros ambientais : a natureza das águas urbanas em Aracaju - Silva, Daniel Almeida da (2016)
Geography has the study of spatiality as a basic premise and scope, therefore, to elect the urban water - resource - as the core of this thesis, we tried to explain the production process of urban space in the city of Aracaju - except the expansion area - using an integrated analysis of society and nature having as bias the discussion of the water issue. They are considered two-way analysis of: i) assessment of the physical dimension, which focuses on morphoclimatic and pedogenic processes and thus comprises the dynamics of environmental components and the city; ii) analysis of the historical dimension, integrated and conclusive of the socioeconomic, political and legal on the current water conditions of the capital, thus linking the urban growth to the occupation of wetlands, burial and straightening of river channels, the quantitative and qualitaty (un)access of water and, finally, the disposal of effluents. Therefore, it was decided to methodologies that respond the research issues, they are: the analysis of Socio-spatiality (1977) by Santos, as well as the analysis of totality grounded by the social metabolism of capital by Mészáros (2002). Aracaju urban site has been characterized by worrying pluvial erosions and hydrodynamic examples, resulting from leads processed by man. Flow problems are constant during the rainy season, in the absence of flow structure in relation to the amount of rainwater that is intensified by the growth of sealing surfaces and consequent trends of rainfall dysrhythmias. In summary, it can be said that the problem of urban water in Aracaju refers to the environmental crisis, here described as a particular form of manifestation of a global and structural crisis, that is, the crisis of the producing societies of goods, that wins special contours on the periphery of the capitalist system. A crisis that has a global dimension, which can be attested by the increasing drinking water demand and the increasingly limited nature of this resource (contradiction that has conferred it a strategic economic value) and also local, since the pattern of social metabolic reproduction of the ongoing capital deepens, rather than to combat the situation of degradation of water in Aracaju.